Gambaran Spiritualitas Lansia Di Panti Sosial Tresna Werdha Khusnul Khotimah Pekanbaru - Vera - Destarina; Agrina - -; Yulia Irvani Dewi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2014)
The purpose of this research is to describe spirituality in social residence Khusnul Khotimah. This research uses a simple descriptive method. The number of samples in this research were 39 elderly people in social residence Khusnul Khotimah Pekanbaru taken by using purposive sampling technique. The data were collected by a questionnaire that consist of 28 questions. Analysis of this research used univariate and frequency distribution. This study use questionnaire spirituality which created by Amir Syam and have the validity tested and reliability. The results showed that 59.0% of elderly have a high spirituality and 41.0% of elderly had low spirituality. Based on the result of this study, it is suggested to the social residence Khusnul Khotimah to provide holistic services to the elderly so that problems that arise in the elderly, especially spirituality can be identified quickly and is expected to prepare health workers, especially rnurses gerontic to provide nursing care related to spirituality, so elderly will be able to maintain their spirituality. Keywords                                :  Elderly, Social residence, Spirituality